Membrane Interactions of the Mason-Pfizer Monkey Virus Matrix Protein and Its Budding Deficient Mutants - Kroupa, Tomáš; Langerová, Hana; Doležal, Michal; Prchal, Jan; Spiwok, Vojtěch; Hunter, Eric; Rumlová, Michaela; Hrabal, Richard; Ruml, Tomáš (Journal of molecular biology, 2016)
Matrix proteins (MAs) play a key role in the transport of retroviral proteins inside infected cells and in the interaction with cellular membranes. In most retroviruses, retroviral MAs are N-terminally myristoylated. This modification serves as a membrane targeting signal and also as an anchor for membrane interaction. The aim of this work was to characterize the interactions anchoring retroviral MA at the plasma membrane of infected cell. To address this issue, we compared the structures and membrane affinity of the Mason-Pfizer monkey virus (M-PMV) wild-type MA with its two budding deficient double mutants, that is, T41I/T78I and Y28F/Y67F. The structures of the mutants were determined using solution NMR spectroscopy, and their interactions with water-soluble phospholipids were studied. Water-soluble phospholipids are widely used models for studying membrane interactions by solution NMR spectroscopy. However, this approach might lead to artificial results due to unnatural hydrophobic interactions. Therefore, we used a new approach based on the measurement of the loss of the 1H NMR signal intensity of the protein sample induced by the addition of the liposomes containing phospholipids with naturally long fatty acids. HIV-1 MA was used as a positive control because its ability to interact with liposomes has already been described. We found that in contrast to HIV-1, the M-PMV MA interacted with the liposomes differently and much weaker. In our invivo experiments, the M-PMV MA did not co-localize with lipid rafts. Therefore, we concluded that M-PMV might adopt a different membrane binding mechanism than HIV-1.
Keywords: Protein Binding; liposome binding; Mutation, Missense; membrane interaction; mutantní proteiny; uvolnění viru z buňky; missense mutace; Liposomes; mastné kyseliny; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Fatty Acids; liposomy; Viral Matrix Proteins; vazba proteinů; Cell Membrane; Phospholipids; buněčná membrána; fosfolipidy; matrix protein; Masonův-Pfizerův opičí virus; Mason-Pfizer monkey virus; Virus Release; proteiny virové matrix; budding; Mutant Proteins